2015
DOI: 10.1175/jpo-d-14-0128.1
|View full text |Cite
|
Sign up to set email alerts
|

Biases in Thorpe-Scale Estimates of Turbulence Dissipation. Part I: Assessments from Large-Scale Overturns in Oceanographic Data

Abstract: Oceanic density overturns are commonly used to parameterize the dissipation rate of turbulent kinetic energy. This method assumes a linear scaling between the Thorpe length scale L T and the Ozmidov length scale L O . Historic evidence supporting L T ; L O has been shown for relatively weak shear-driven turbulence of the thermocline; however, little support for the method exists in regions of turbulence driven by the convective collapse of topographically influenced overturns that are large by open-ocean stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 43 publications
10
86
0
Order By: Relevance
“…Turbulent quantities are important to the energy balance of the global ocean and are prevalently parameterized in largescale circulation models. Results from previous work using finestructure methods to interpret mixing rates have recently been shown to be biased high (Frants et al (2013), Mater et al (2015), Waterman et al (2014)), often by up to two orders of magnitude. This work has revisted the values and patterns of mid-depth mixing in this region to inform modeling efforts and large-scale estimates of vertical diffusivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbulent quantities are important to the energy balance of the global ocean and are prevalently parameterized in largescale circulation models. Results from previous work using finestructure methods to interpret mixing rates have recently been shown to be biased high (Frants et al (2013), Mater et al (2015), Waterman et al (2014)), often by up to two orders of magnitude. This work has revisted the values and patterns of mid-depth mixing in this region to inform modeling efforts and large-scale estimates of vertical diffusivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work has shown the potential for biases between mixing rates inferred from both of those methods and those from direct measurements. Mater et al (2015) found Thorpe scale methods overestimate mixing rates when compared to direct measurements especially in the presence of large overturns. In the Southern Ocean, mixing rates inferred from finescale parameterizations are shown to overestimate those from microstructure measurements by as much as 1-2 orders of magnitude (Frants et al, 2013).…”
Section: Introductionmentioning
confidence: 88%
“…The measured stratification is thus representative of the near-bottom region, which is also small compared to the full water depth (about 100 m compared with a total depth of 920 m). This approach is more or less similar to some direct numerical simulation (DNS) studies using Thorpe reordering on a fixed domain rather than on single overturns (e.g., Mater et al 2013). By differencing the potential energy contained in the raw and reordered density profiles, it is also possible to (Dillon 1984;Crawford 1986;Dillon and Park 1987) …”
Section: Datamentioning
confidence: 95%
“…This reflects passive scalar turbulence dominated by shear (Tennekes and Lumley, 1972). After sufficient averaging this passive scalar turbulence is efficient (Mater et al, 2015). At intermediate depth levels and in short frequency ranges of the spectral data, slopes vary between −2 and −1.…”
Section: Spectral Overviewmentioning
confidence: 99%